Impact of climate factors, breed, and boar utilization frequency on semen quality and sperm morphology - Petrović Aleksandra; Bogdanović Vladan; Radović Čedomir; Stanković Branislav; Živković Vladimir; Stojiljković Nenad; Gogić Marija (Biotechnology in Animal Husbandry, 2024)
The primary objective of this research was to evaluate boar ejaculate variability and the occurrence of anomalies in spermatozoa, considering climatic factors during spermatogenesis breed, and utilization frequency. This study involved 17 boars (n=129 ejaculates) and fertility testing was conducted during the most critical period of the year, from August to October. The observed sperm characteristics included: ejaculate volume (VOL), sperm concentration (CON, spermatozoa/ml), total number and number of functional spermatozoa (NT, NF), percentage of sperm motility in the native ejaculate and after dilution (MOTN, MOTD), number of produced doses (NPD), percentage of dead and live spermatozoa (PM, PZ), and sperm anomalies. The assessment of the effect was performed using a General Linear Model procedure. The breed did not influence sperm variability, while the frequency of boar utilization impacted on the occurrence of secondary anomalies. The determined regression coefficient indicated that extending the interval by one day increased PPPK by 0.340-0.348%. The maximum daily temperature during semen collection (model 1) and the value of the TH index during semen collection (model 3) influenced ejaculate volume. An increase of one ℃ in temperature, or one unit in THI value, led to a (p<0.05) increase in VOL by 3.540 ml and 2.798 ml, respectively. Furthermore, the maximum daily temperature (model 2) and the TH index value (model 4) at the beginning of the epididymal phase of spermatogenesis had an impact on semen motility, as well as the percentage of live and dead spermatozoa.